Service Quality and Customer Satisfaction in Nigerian Mobile Telephony - Alabar; Timothy, T.; Egena, Ode; Gbande; Richard, I. (British Journal of Marketing Studies, 2016)
The Telecommunication industry in Nigeria has developed to be very competitive, as different Telecom companies jostle for the attention of subscribers. However, one of the key challenges confronting these companies is how they manage their service quality, which holds a grea deal to customer satisfaction. It is against this backdrop that this research seeks to empirically measure how service qualiy/delivery impact on customer satisfaction of Mobile Telecommunication providers in Nigeria.  The data used for this study were obtained using a structured survey questionnaire. The questions were close ended and used a 5 point Likert-scale. The sample consists of 532 mobile subscribers in Nigeria, using a simple random sampling technique spread across all the six geo-political zones in the country while a proportionate sampling approach was adopted by the researcher to give a fair representation to the service providers using the proportionality formula. The data obtained from the survey were analysed using the Statistical Package for Social Sciences (SPSS), Version 20. The survey was restricted to subscribers using the four major GSM mobile phone operators. The research  determined that a relationship exist between service quality/delivery and customer satisfaction, also between SERVQUAL reliability dimension and customer satisfaction and between customer satisfaction and switching intention among mobile phone users in Nigeria. The results have indicated that the two constructs ( SQ and CS ) are undeniably independent but are closely related and without a doubt, potential partners, implying that an increase in one is likely to cause a change in another. It is therefore recommended that with the ever-increasing influence of the Nigeria Communications Commission (NCC),and the continous complying with  is one major strategy that the companies must adopt to remain cost-effective.